2019
DOI: 10.1111/sltb.12599
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self‐Injury‐Related Differences in the Experience of Negative and Positive Emotion

Abstract: Objective Emotional experience is argued to contribute to the initiation and maintenance of nonsuicidal self‐injury (NSSI). We investigated whether individuals with/without a history of NSSI differed in their dispositional experience of negative and positive emotion, as well as their state responses to negatively and positively valenced movie clips. Method Undergraduates (n = 214, Mage = 21.33, 73.8% female, 35.5% reporting NSSI) completed measures of NSSI and dispositional emotional experience. Participants a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 40 publications
(72 reference statements)
7
51
1
Order By: Relevance
“…However, a number of factors may account for the discrepancy between Boyes and colleagues' (Boyes et al, 2020) study and the current study. Most importantly, the measure of emotion reactivity for positive and negative emotions used by Boyes and colleagues (Boyes et al, 2020), the Emotion Reactivity Intensity and Perseverance Scale (Ripper et al, 2018), relied heavily on social comparison (i.e., "When exposed to a situation that would make the 'average' person experience this feeling, how likely is it that you will experience this particular feeling?") whereas the Emotion Reactivity Scale (Nock et al, 2008) used in the current study focused solely on participants' own experiences of positive and negative emotion reactivity.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…However, a number of factors may account for the discrepancy between Boyes and colleagues' (Boyes et al, 2020) study and the current study. Most importantly, the measure of emotion reactivity for positive and negative emotions used by Boyes and colleagues (Boyes et al, 2020), the Emotion Reactivity Intensity and Perseverance Scale (Ripper et al, 2018), relied heavily on social comparison (i.e., "When exposed to a situation that would make the 'average' person experience this feeling, how likely is it that you will experience this particular feeling?") whereas the Emotion Reactivity Scale (Nock et al, 2008) used in the current study focused solely on participants' own experiences of positive and negative emotion reactivity.…”
Section: Discussioncontrasting
confidence: 88%
“…Furthermore, differences in sample demographics may also account for this discrepancy in findings. Specifically, although the present study had an exclusively female sample of participants, Boyes and colleagues (Boyes et al, 2020) only had a majority of female participants (73.8%), which may have influenced findings given that studies have demonstrated potential gender differences in the experience of NSSI (e.g., Sornberger et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations